Psychological Overview of Children in Conflict with the Law at Ternate Special Child Development Institution - Mu'mina Kurniawati S. J. Kahar; Salwa Muin (Fakultas Ushuluddin, Adab dan Dakwah - Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study aims to identify early psychological conditions among children at the Ternate Class II Special Child Development Institution (LPKA) and to describe the emotional, social, and behavioural responses that emerge during development. The study used a qualitative descriptive approach with purposive sampling, involving 12 children aged 13–18 years who met specific criteria and were willing to participate. Data collection was carried out through in-depth interviews and non-participant observation, using semi-structured interview guidelines, observation sheets, and field notes. Data were analysed using thematic analysis, including transcription, data reduction, coding, and theme extraction. The research findings indicate that most children experience emotional vulnerabilities such as fear, guilt, and anxiety; a need for social acceptance and emotional support; and adaptive skills and potential resilience that develop through positive interactions in institutional settings. Key contributing factors include previous experiences of violence, lack of family support, and social stigma. These findings underscore the importance of ongoing psychological support, a humanistic counselling approach, and consistent social support to improve children's psychological well-being during and after counselling.